Existential Anxiety and the Dynamics of Religiosity: A Philosophical–Theological Perspective - Muslih , Mohammad Muslih; Naim, Ngainun; Affandi, Muchammad Taufiq (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
This article explores the dynamic role of religion in responding to contemporary human anxiety, particularly through a reflection on the interrelation between reason, language, and faith. In a modern context characterized by fragmentation of meaning and psychological stress, religion is often perceived as outdated or merely symbolic. This paper argues that the root of the problem lies not in religious teachings themselves, but in how they are understood, conveyed, and lived. Using a conceptual-qualitative and interdisciplinary approach that integrates linguistic studies, existential philosophy, and the psychology of religion, this study emphasizes the importance of religion as a space for dialogue and responsiveness rather than a system that silences questions. The article discusses three main subthemes: (1) the role of language as a medium of existential expression in religion; (2) the function of reason in interpreting dynamic faith; and (3) religion’s role as a responsive answer to human anxiety. The analysis of these subthemes suggests that mature religiosity promotes openness, spiritual freedom, and moral maturity. Thus, this article offers a framework for interpreting religion that is not only theologically relevant but also existentially and ethically impactful in daily life.